Ecology of semiosphere: tradition and new approaches - Girutskij, Anatolij A. (Journal of the Belarusian State University. Ecology, 2019)
The article discusses such issues as semiosphere as a conceptual notion of semiotics, the ratio of the semiosphere and the biosphere, the semiosphere and the noosphere. A general description of fundamental laws of ecology as a science, their place in the universe of knowledge and their manifestation in the semiosphere is given. In particular, it is argued that the first law of ecology «everything is connected with everything» is demonstrated in the fact that the basis of the connection of «everything is in everything» is information, the universal carrier of which is the word. It is concluded that the word matrix as an ideal structure exists in the human mind in the form of a hologram associated with the neural networks of the brain. Within the framework of the first law of ecology, the essence of the word as a universal matrix of the macrocosm is characterized. The issues of the origin of the ecological approach to the semiosphere are considered using the example of interaction of language and some other sign systems with religion. Conclusions are drawn about the necessity to improve the ecological protection of the semiosphere as part of the universe, to develop scientific research and practical studies in this direction, to expand specific research in the field of ecolinguistics and ecology of culture.
Keywords: semiosphere; semiotics; biosphere; noosphere; ecology; laws of ecology; word matrix; hologram; language matrix; matrix of the Absolute; the ecology of language; aniconism; ecology of religion